Cultural and economic integration of immigrants in Canada: "do you play hockey?" - Irakli Japaridze; Uma Kaplan (Journal for Labour Market Research, 2023)
This paper studies whether acculturation by immigrants and other minority groups is associated with economic integration in Canada. We examine immigrants' participation in winter sports, particularly hockey, as a proxy for acculturation given that these sports are popular in Canada but are rarely watched or practiced in the origin countries of many immigrants to Canada. Using the Canadian Community Health Survey, we find that practicing winter sports has a positive effect on the earnings of immigrants and other minority groups. Specifically, practicing winter sports closes the income gap between immigrants and natives. However, the gap does not decrease for visible-minority immigrants, suggesting that acculturation might not be sufficient to combat racial biases.
Keywords: J15; J71; J31; 330; Immigrant integration; Assimilation; Discrimination; Acculturation